The politics of truth and reconciliation in South Africa : legitimizing the post-apartheid state - Wilson, Richard, 1964- (Cambridge ; New York : Cambridge University Press, 2001)
"The South African Truth and Reconciliation Commission (TRC) was set up to deal with the human rights violations of apartheid during the years 1960-1994. However, as Wilson shows, the TRC's restorative justice approach to healing the nation did not always serve the needs of communities at a local level. Based on extended anthropological fieldwork, this book illustrates the impact of the TRC in urban African communities in the Johannesburg area. While a religious constituency largely embraced the Commission's religious-redemptive language of reconciliation, Wilson argues that the TRC had little effect on popular ideas of justice as retribution. This provocative study deepens our understanding of post-apartheid South Africa and the use of human rights discourse. It ends on a call for more cautious and realistic expectations about what human rights institutions can achieve in democratizing countries."--Jacket.
1. Human rights and nation-building -- 2. Technologies of truth : the TRC's truth-making machine -- 3. The politics of truth and human rights -- 4. Reconciliation through truth? -- 5. Reconciliation in society : religious values and procedural pragmatism -- 6. Vengeance, revenge and retribution -- 7. Reconciliation with a vengeance -- 8. Conclusions : human rights, reconciliation and retribution.
Includes bibliographical references (pages 246-262) and index.
Keywords: South Africa. -- Truth and Reconciliation Commission; Since 1994; Reconciliation -- Political aspects -- South Africa; Apartheid -- South Africa; Post-apartheid era -- South Africa; Retribution; Reward (Theology); Punishment; Truth and Reconciliation Commission